2021
DOI: 10.1186/s40635-020-00364-6
|View full text |Cite
|
Sign up to set email alerts
|

Bedside monitoring of lung volume available for gas exchange

Abstract: Background Bedside measurement of lung volume may provide guidance in the personalised setting of respiratory support, especially in patients with the acute respiratory distress syndrome at risk of ventilator-induced lung injury. We propose here a novel operator-independent technique, enabled by a fibre optic oxygen sensor, to quantify the lung volume available for gas exchange. We hypothesised that the continuous measurement of arterial partial pressure of oxygen (PaO2) decline during a breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The increasing interest in personalising ventilation is likely to lead to more complex automated assessments derived from the ventilator being integrated with non-invasive imaging at the bedside over time. New devices under development can aid the assessment of recruitability 165 and overdistension 166 at the bedside by measuring intratidal fluctuations in PaO 2 . Other studies have used electroencephalography to directly measure oscillatory neural activity in response to inspiratory loading or deliberate induction of asynchrony.…”
Section: Multimodal Monitoring During Vv Ecmomentioning
confidence: 99%
“…The increasing interest in personalising ventilation is likely to lead to more complex automated assessments derived from the ventilator being integrated with non-invasive imaging at the bedside over time. New devices under development can aid the assessment of recruitability 165 and overdistension 166 at the bedside by measuring intratidal fluctuations in PaO 2 . Other studies have used electroencephalography to directly measure oscillatory neural activity in response to inspiratory loading or deliberate induction of asynchrony.…”
Section: Multimodal Monitoring During Vv Ecmomentioning
confidence: 99%
“…Although considered as a "gold standard" for lung volume assessment, it is important to highlight that CT scans accurately measures the "anatomical lung volume", in contrast with MBNW technique, or other gas-dilution technique, where the lung volume measured contributes to ventilation, i.e., "ventilable lung volume" [4]. Thus, in the presence of overinflated lung areas (at high PEEP levels) the "anatomical lung volume" is expected to be different from the "ventilable lung volume" [7,28]. The current study supports previous results, since the bias observed between the tested methods was independently related to the amount of overinflation at end-expiration, it may be hypothesized that overinflated lung areas did not participate to nitrogen mixing during washin-washout, which may explain EELV underestimation at high PEEP.…”
Section: Reliability and Trending Ability Of Eelv Mbnwmentioning
confidence: 99%
“…The lung is a very crucial organ of the human body. It is situated in the thorax region and primarily responsible for respiration [ 1 ]. All the cells in the body require oxygen to carry out various activities.…”
Section: Introductionmentioning
confidence: 99%